PENERAPAN METODE ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI PADA BABY AND MOM CARE ABC - Nurazizah, Siti; Yuliarida, Nafisah Dwi; Amidia, Nadira Aisha; Rahmawati, Nurmala Dewi; Rizaldi, Muhammad Rama; Fajriatama, Tegar Dwi; Situngkir , Tiar Lina (Value : Journal of Management and Business, 2024)
Our research focuses on the issue of utilizing Activity Based Costing in Baby and Mom Care to determine Production costs. The study aims to compare the production cost using the Activity Based Costing (ABC) approach with the company's conventional method. A general description of Baby and Mom Care ABC, information about the company's founding and history, vision and mission, products, and their benefits are all included in this research, which uses a qualitative research methodology. Quantitative data used in the study includes production statistics for Baby and Mom Care ABC in 2022, which include details about the usage of raw materials, direct labor costs, and factory overhead costs. Using a variety of data collection techniques, including interviews and documents, we were able to gather primary and secondary data for our study. The study's findings compare the production costs using traditional and activity-based costing techniques for baby and mom care items with their retail prices, which are 25,000 for beetroot juice and 15,000 for turmeric herbal medication, respectively. Nevertheless, compared to the Traditional technique, the cost of goods produced utilizing the Activity Based Costing method is higher. The outcomes of the Activity Based Costing Method outperform those of the Traditional Method. This is because manufacturer overhead payments differ fundamentally. The Activity Based Costing Method employs many cost drivers to provide more precise assignments than the Traditional Method, which simply uses production units as a cost driver.